Suppression Effects of Pandanus Amarylfolius and Strobilanthes Cripus Extracts on the Growth of Breast Cancer Cells by Inducing p53-Mediated Apoptotic Pathway - Chong, Hueh Zan (2010)
Pandanus amaryllifolius (PA) or commonly known as daun pandan is a common culinary plant in South-east Asia from the screw pine family. The leaves of PA are added to cooking to give a pleasant nutty aroma, reminiscent to fresh hay. Besides for aromatic value, PA has a long history in local traditional medicine system alleviating ailments and promotion of well-being. Meanwhile, Strobilanthes crispus ZII 109 (L) Bremek (Acanthaceae) is a native plant to countries from Madagascar to Indonesia. Strobilanthes crispus (SC) or pecah beling has long been used as medicinal plants against various conditions and cancer. In this research, chemopreventive properties of Pandanus amarylfolius and Strobilanthes cripus extracts were investigated via screening against a panel of human cancer cell lines and the normal fibroblast cells to screen for selective cytotoxicity and anti-proliferative activity. Both ethanolic PA and SC extracts were found to display selective cytotoxicity and anti-proliferative against breast cancer cells but not on normal cells. In the sample treated with PA for 72 hours, MTT 3-(4 ,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay showed that cytotoxicity activity of PA was found to be effective against non-hormone dependent breast cancer cell lines MDA-MB-231, 50% inhibition of cell growth at a concentration of (IC50=90 μg/mL). Anti-proliferative activities of PA in MDA-MB-231 cells were further evaluated using the colorimetric pyrimidine analogue BrdU incorporation. Exposure of PA extract at IC50 concentration (90 g/mL) resulted in a decrease in percentage of cells that underwent DNA synthesis in the cell cycle (S phase). Therefore, suggesting PA extract inhibited proliferation of MDA-MB-231. Further investigation of chemoprevention activities focusing on modulations of cell cycle events and induction of apoptosis was carried out. Flow-cytometry cell cycle RNAase/PI assay of MDA-MB-231 cells treated with PA extract (90 g/mL) revealed alteration in cell cycle distribution and accumulation of cell population at G1 phase. G1 arrest of treated MDA-MB-231 cells was found to involve upregulation of cyclin dependent kinase inhibitors (CKI) p21 protein level and in the inhibition of cdk2 and 4 activities. At 48 and 72 hr experimental time point, exposure of PA (90 g/mL) towards MDA-MB-231 cells was found to induce cell death. Apoptosis event was assessed by various assays portraying different apoptotic features. Detection of apoptosis was carried out by Annexin V/FIT-C staining, Acridine orange/Propidium iodide staining as well as DNA ladder assay and was confirmed using TUNEL assay. Apoptosis induction was found to involve activation of caspase cascades and release of Cytochrome C. The molecular mechanisms in the induction of apoptosis by PA in MDA-MB-231 cells were found to involve upregulation of tumour suppressor protein p53 and pro-apoptotic bax protein while a reduction in the expression of inhibitor of apoptosis XIAP protein. On the other hand, exposure of SC extract (30 g/mL) resulted in 50% inhibition of cell growth in hormone dependent breast cancer cell line MCF-7. Further analysis indicated the presence of subG1 population in MCF-7 cells treated with SC extract (30 g/mL), a classical feature of apoptotic cells. Detection of apoptotic MCF-7 cells was also apparent in flow cytometry Annexin V/FIT-C staining and via detection of double or single DNA break strands in TUNEL assay. Mitochondrial activated apoptosis induction by SC in MCF7 cells was found to involve activation of caspases and release of Cytochrome C into the cytosol thus, activating initiator and effector caspase 3/7. Upregulation of tumour suppressor p53 protein was detected upon SC exposure however, apoptosis induction in treated MCF-7 cells was found to be p53 transcriptive independent as pro-apoptotic bax and Bcl-2 protein were not activated upon activation of apoptosis machinery. In this research, the targeted modulation or restoration of the intracellular signaling network by Pandanus amaryllifolius and Strobilanthes cripus extracts towards breast cancer cells offered a potential strategy in preventing abnormal cell proliferation and promoting cell death of neoplastic cells in an in-vitro model.